ANALISIS STRATEGI DAN POLA KOMUNIKASI GURU DALAM PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN SISWA TUNARUNGU DI KELAS V SLB MUZDALIFAH MEDAN - Rutmay Prina Br Sembiring; Dinda Alvionita Lubis; Nabilah Hana Ariqah; Ningsih Mayasari; Ramadhani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers' communication strategies and patterns in learning to improve the understanding of deaf students in grade V of Muzdalifah Special Needs School. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation with teachers as the main informants. The results of the study indicate that the communication strategies used by teachers include total communication, the use of visual media, and individual approaches tailored to student characteristics. One of the research subjects was a student named Chelsi who is categorized as moderately deaf. The communication pattern applied by teachers is two-way, but is still dominated by the teacher. The assessment system applied is the same as for regular students, with additional assessments on aspects of habits and behavior. The results of the study indicate that appropriate communication strategies can improve student understanding, but more adaptive learning innovations are still needed.